The Design and Research of Ocean Observation Buoy Operation Status Monitoring System. Issue 1 (July 2020) - Zhang, Yimeng; Liu, Lingfeng; Guan, Yi; Song, Kun; Xu, Jinxing
Abstract: At present, there is no unified monitoring system for ocean observation buoys in China. Some of the existing monitoring systems are only decentralized management and control of observation buoys, and their accuracy and management scope cannot meet the needs. This article describes the design and development process and technical details of the three main modules of the system's real-time monitoring, operation and maintenance management and intelligent decision-making. This system can obtain the real-time status of the entire network of buoys in time, so it can find faults in time, and eliminate and isolate the faults in time to reduce the losses caused by the buoy faults to the entire marine environmental protection system.